Alternative mitochondrial quality control mediated by extracellular release. Issue 10 (3rd October 2021) - Choong, Chi-Jing; Okuno, Tatsusada; Ikenaka, Kensuke; Baba, Kousuke; Hayakawa, Hideki; Koike, Masato; Yokota, Mutsumi; Doi, Junko; Kakuda, Keita; Takeuchi, Toshihide; Kuma, Akiko; Nakamura, Shuhei; et al.
ABSTRACT: Mitochondrial quality control, which is crucial for maintaining cellular homeostasis, has been considered to be achieved exclusively through mitophagy. Here we report an alternative mitochondrial quality control pathway mediated by extracellular mitochondria release. By performing time-lapse confocal imaging on a stable cell line with fluorescent-labeled mitochondria, we observed release of mitochondria from cells into the extracellular space. Correlative light-electron microscopy revealed that majority of the extracellular mitochondria are in free form and, on rare occasions, some are enclosed in membrane-surrounded vesicles. Rotenone- and carbonyl cyanide m-chlorophenylhydrazone-induced mitochondrial quality impairment promotes the extracellular release of depolarized mitochondria. Overexpression of PRKN (parkin RBR E3 ubiquitin protein ligase), which has a pivotal role in mitophagy regulation, suppresses the extracellular mitochondria release under basal and stress condition, whereas its knockdown exacerbates it. Correspondingly, overexpression of PRKN-independent mitophagy regulators, BNIP3 (BCL2 interacting protein 3) and BNIP3L/NIX (BCL2 interacting protein 3 like), suppress extracellular mitochondria release. Autophagy-deficient cell lines show elevated extracellular mitochondria release. These results imply that perturbation of mitophagy pathway prompts mitochondria expulsion. Presence of mitochondrial protein can also be detected in mouse sera. Sera of PRKN-deficient mice contain higher level of mitochondrial protein compared to that of wild-type mice. More importantly, fibroblasts and cerebrospinal fluid samples from Parkinson disease patients carrying loss-of-function PRKN mutations show increased extracellular mitochondria compared to control subjects, providing evidence in a clinical context. Taken together, our findings suggest that extracellular mitochondria release is a comparable yet distinct quality control pathway from conventional mitophagy. Abbreviations: ACTB: actin beta; ANXA5: annexin A5; ATP5F1A/ATP5A: ATP synthase F1 subunit alpha; ATG: autophagy related; BNIP3: BCL2 interacting protein 3; BNIP3L/NIX: BCL2 interacting protein 3 like; CCCP: carbonyl cyanide m-chlorophenylhydrazone; CM: conditioned media; CSF: cerebrospinal fluid; DMSO: dimethyl sulfoxide; EM: electron microscopy; HSPD1/Hsp60: heat shock protein family D (Hsp60) member 1; KD: knockdown; KO: knockout; MAP1LC3A/LC3: microtubule associated protein 1 light chain 3 alpha; MT-CO1: mitochondrially encoded cytochrome c oxidase I; NDUFB8: NADH:ubiquinone oxidoreductase subunit B8; OE: overexpression; OPA1: OPA1 mitochondrial dynamin like GTPase; OXPHOS: oxidative phosphorylation; PBS: phosphate-buffered saline; PB: phosphate buffer; PD: Parkinson disease; PINK1: PTEN induced kinase 1; PRKN: parkin RBR E3 ubiquitin protein ligase; RB1CC1/FIP200: RB1 inducible coiled-coil 1; SDHB: succinate dehydrogenase complex iron sulfur subunit B; TOMM20: translocase of outer mitochondrial membrane 20; TOMM40: translocase of outer mitochondrial membrane 40; UQCRC2: ubiquinol-cytochrome c reductase core protein 2; WT: wild-type